Exploring disparities in satisfaction with obstetric-gynecological care among insured and uninsured women in Almaty, Kazakhstan: a comparative cross-sectional study - Sholpan Aliyeva; Sholpan Aliyeva; Vyacheslav Lokshin; Maksut Kamaliev; Sholpan Sarmuldayeva; Gani Kaldybayev; Oxana Tsigengagel (Frontiers in Global Women's Health)
BackgroundPatient satisfaction is a key indicator of healthcare quality. Although crucial, limited research has explored factors contributing to satisfaction disparities in outpatient obstetric-gynecological care, particularly in Kazakhstan. The objective of the study is to explore disparities in satisfaction with obstetric-gynecological care between insured and uninsured women in Almaty, Kazakhstan, and to identify the key determinants of patient satisfaction.MethodsA cross-sectional survey was conducted among 107 insured and uninsured patients over three months in early 2024 at a hospital in the Almaty region, Kazakhstan. Using a five-point Likert scale, a structured questionnaire assessed socio-demographics, patient-reported experiences with the care process, and overall satisfaction across 16 dimensions. The survey instrument was pilot-tested and demonstrated strong internal consistency (Cronbach's alpha = 0.83). Chi-square tests examined associations, and multivariable logistic regression identified key predictors of patient satisfaction.ResultsA multivariable analysis revealed a “satisfaction paradox”: insured patients had lower odds of being satisfied compared to uninsured patients (AOR = 0.15, 95% CI: 0.03–0.81). Specifically, a lack of insurance was associated with higher reported satisfaction in doctor-patient communication (OR = 1.8) and nursing care (OR = 2.1). Other significant predictors of satisfaction included having kidney disease and a shorter hospital stay.ConclusionsOur findings suggest that expanding insurance coverage is necessary for access but insufficient for ensuring patient satisfaction. The observed “satisfaction paradox” highlights that policy must adopt a dual focus: promoting enrolment while simultaneously improving the quality of patient-provider interactions to meet the higher expectations of insured patients.